Mil tons de Minas: Milton Nascimento e o Clube da Esquina: cultura, resistência e mineiridade na música popular brasileira - Oliveira, Rodrigo Francisco de (2006)
Between 1967 and 1978, Brazilian culture and music were reevaluated. Also in this period, Clube da Esquina a musical group from the state of Minas Gerais whose musical production is this work s subject matter begun its activities. Our goal is to understand the songs written by this group in its historical and production context, identifying characteristics that distinguish it as a cultural movement. For that, we try to understand cultural industry and the development of capitalism and arts during military regimen in Brazil with a focus on censorship, technical, aesthetical changes in the field of arts and music, ideologies of the main groups opposed to the dictatorship in Brazil, and artistic universe with its vicissitudes. Methodological procedures included bibliographic reviewing and analysis of Clube da Esquina s discography sleeves, lyrics, arrangement structure and orchestrations produced between the beginning of AI-5 and the political opening in the late 1970s. With this study, we succeeded in verifying certain lack of researches on the Clube da Esquina, above all works dealing with the formal elements of the group work. Our analysis suggests that this movement has kept a dialogue with literature, dance and cinema; it also suggests that many of the group s songs establish a dialogue with the listener and a relationship between artistic production and historical time. Besides, this study shows that, in incorporating Minas Gerais popular culture, Clube s music places this cultural movement between world culture e Minas Gerais culture, in an elastic frontier that separates and unites popular and vanguard characteristics.